2006
DOI: 10.1002/biof.5520260301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of baseline serum levels of Se on markers of eccentric exercise‐induced muscle injury

Abstract: Inflammation and oxidative stress have been implicated in the mechanism of eccentric exercise-induced muscle injury. This study examined whether baseline serum levels of selenium (Se), a trace element that participates in both antioxidant and anti-inflammatory systems, affects the overall response to injury. Thirteen males performed 36 maximal eccentric actions with the elbow flexors of the non-dominant arm on a motorized dynamometer. Venous blood samples were collected immediately before and after exercise at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 37 publications
2
2
0
1
Order By: Relevance
“…Our results show a higher mean serum selenium concentration (91.8 μg/L, N= 506) compared to the studies of Van Cauwenbergh et al [7] (∼68 μg/L, N=160) and Kostakopoulos et al [16] (∼55 μg/L, N=100), while studies of Schrauzer et al [8] (∼130 μg/L) and Kallistros et al [15] (∼136 μg/L, N=40) have demonstrated mean serum selenium concentrations which is well within the range of the plasma Se levels observed by our group in the age group between 20 and 40 years.. Finally, our results are in agreement with the study of Milias et al [17] (∼80 μg/L). A number of reasons may explain the different results of our study compared to the previous studies on Greek populations, such as the much lower number of participants of the other studies compared to ours and also the different nutritional habits of Greeks 15-20 years ago when the previous studies were published.…”
Section: Discussionsupporting
confidence: 95%
“…Our results show a higher mean serum selenium concentration (91.8 μg/L, N= 506) compared to the studies of Van Cauwenbergh et al [7] (∼68 μg/L, N=160) and Kostakopoulos et al [16] (∼55 μg/L, N=100), while studies of Schrauzer et al [8] (∼130 μg/L) and Kallistros et al [15] (∼136 μg/L, N=40) have demonstrated mean serum selenium concentrations which is well within the range of the plasma Se levels observed by our group in the age group between 20 and 40 years.. Finally, our results are in agreement with the study of Milias et al [17] (∼80 μg/L). A number of reasons may explain the different results of our study compared to the previous studies on Greek populations, such as the much lower number of participants of the other studies compared to ours and also the different nutritional habits of Greeks 15-20 years ago when the previous studies were published.…”
Section: Discussionsupporting
confidence: 95%
“…Therefore, selenium must necessarily have remarkable effects on muscle functions. The fact that selenium deficiency in exercising individuals has been shown to lead to impairments in muscle contractions [39] is an important report that supports our argument. Hornberger et al [33] reported that selenium deficiency led to a decline in selenoprotein levels, which resulted in a deficiency in muscle functions.…”
Section: Discussionsupporting
confidence: 77%
“…This review outlined a wide assortment of ingredients, functional foods, and dietary supplements that have been shown to affect EIMD-related outcomes, with varying levels of success. In addition to the topics covered in the present review, many emergent nutritional and supplementation strategies have not been fully explored, including black tea-sourced polyphenols [161], blueberries [162], chondroitin sulfate [163], high chlorogenic acid coffee [164], fasting [165], garlic [166], leucine metabolites such as HICA [167], lemon verbena [168], lychee [169], mate tea [170], pequi fruit [171, 172], quercetin [173], saffron [174], selenium [175], sesame [176], spinach [177], and tomato juice [178, 179]. Future research in these nascent areas may shed new light on potential treatment options for EIMD.…”
Section: Discussionmentioning
confidence: 99%